Macroeconomic Factors as Moderators: SCM Impact on Shipping Industry Performance - Supeni Purwaningsih, Endah (International Journal of Economics and Management Research, 2024)
Building and development in the maritime aspect become one of the agendas in Indonesia which are known as Nawa Cita. Furthermore, Ministry Regulation number 80, 2015 has supported the increased number of inter-island sea transportation which cause higher competition among cruise companies. In line with that, every company is forced to give more value than the competitor through the right choice of strategy. Therefore, the study aimed to examine and analyze the effect of supply chain management on competitive advantage and a firm’s performance; the effect of competitive advantage on a firm’s performance, and the role of macro-economics as moderating variable. Moreover, the study was explanatory research that discussed the relationship between variables through hypothesis tests. The data collection technique used saturated sampling (census). Additionally, there were 15 companies with 7 years of observation (2013-2019) as the sample. In total, 105 financial statements were observed. In addition, the data analysis technique used Partial Least Square (PLS). As a result, supply chain management affected the competitive advantage of cruise companies. However, both supply chain management and competitive advantage did not affect the performance of cruise companies. On the other hand, external factors of macro-economics could support the implementation of supply chain management in increasing the competitive advantage of cruise companies. Besides, they could also back up the implementation of supply chain management as well as a competitive advantage in increasing the performance of cruise companies